Effect of inulin, galacto oligosaccharides and iron fortification on iron deficiency anemia among women of reproductive age; a randomized controlled trial - Iqbal, Sehar; Ahmed, Waqas; Zafar, Saira; Farooq, Umar; Abid, Juweria; Shah, Hassan Bin Usman; Akram, Sajeela; Ghazanfar, Madiha; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2022)
Iron supplementation and fortification are the well-known approaches to treat anemia in women of reproductive age. The objective of this Randomized Controlled Trial (RCT) was to evaluate the cumulative effects of prebiotics and iron fortification among women of reproductive age. For this purpose, a total of 75 iron deficient women of childbearing age were recruited and randomly were divided into 5 groups (4 treatment groups and 1 control group). Four different types of fortified wheat flour were prepared using two iron fortificants (NaFeEDTA and FeSO4) and two prebiotics Inulin and Galacto oligosaccharides (GOS), while control group was treated with iron fortified flour without any prebiotics. Blood samples were collected from overnight fasted women on monthly basis up to 90 days. Hematological indices such as Hemoglobin (Hb), Hematocrit, Red Blood Cell (RBC) Count and Mean Corpuscular value (MCV), as well as iron biomarkers including serum iron, ferritin, transferrin, and Total Iron Binding Capacity (TIBC) were evaluated for analyses. The results showed a considerable positive improvement in relation to all iron biomarkers as well as hematological indices among the treatment groups (P-value < 0.05) as compared to control group. A maximum Hb (11.86±0.24mg/dL), and hematocrit value (35.06±1.32%), was reported in group G3 that was treated with fortified wheat at the dose of 963mg/kg GOS+15ppm FeSO4. Highest mean values for RBC Count (4.73±0.41mil/mm3), MCV (81.41±3.21fL), serum iron (75.62±2.79μg/dL), serum transferrin (16.82±0.30mg/dL), and TIBC (403.68±7.27μg/dL) were observed in G4 group receiving the fortified wheat dose at 963mg/kg GOS+30ppm FeSO4 level. The study concluded that prebiotic fortification along with iron salts helped to enhance iron absorption among anemic women of reproductive age.